Phase Structures of Nascent Polyethylene Powder Studied by Wideline Proton NMR - 严小伟 王靖岱 任晓红 阳永荣 蒋斌波 VODA, Mihai Adrian BERTMER, Marko STAPF, Siegfried (Chinese journal of chemistry, 2007)
The wideline proton NMR spectra of polyethylene powder samples were analyzed in terms of contributions from three components： （1） a rigid part with immobile chains, （2） a soft region with liquid-like character which produces a Lorentzian contribution to the spectrum, and （3） an intermediate region in which the rotation of methylene groups about C-C bonds is partially hindered. The relative mass fractions as well as chain mobilities varied greatly among samples produced by different polymerization techniques. The NMR crystallinity agreed well with that estimated by WAXD and was much higher than DSC crystallinity, indicating an inclusion of the contribution from a crystalline-amorphous interphase. The crystalline defects in the rigid part could be significantly affected by processing parameters when employing the same type of polymerization technique. The intermediate region in the NMR spectra was analyzed according to the comparison between bimodal high density polyethylene and corresponding linear unimodal one. It was found that the mass fraction of the NMR interphase could be an indication of the percentage of tie molecules between crystalline lamellae and thus may significantly affect the mechanical properties of polymeric material.